Labour and perinatal outcome in women at term with one previous lower-segment Caesarean: a review of 1000 consecutive cases - Tan, P.C.; Subramaniam, R.N.; Omar, Siti Zawiah (Wiley, 2007)
Objective: To compare the outcome in 1000 women at term with one lower transverse Caesarean that was suitable for a trial of labour. Methods: One thousand consecutive women with one previous scar suitable for a trial of labour delivering in our centre from June 2002 to December 2005 were identified from the labour ward register. Data were retrieved from patients' charts, and neonatal admissions were determined. Results: In the study, 76.8 of women underwent a trial of labour, with a 71.2 vaginal birth rate. Hospital stay was shorter with a trial of labour. The three perinatal deaths (0.4; P = 1.0) occurred in the trial of labour group. Compared to elective repeat Caesareans, successful vaginal births after trial of labour were associated with less neonatal admission, reduced blood transfusion requirement and shorter hospital stay; emergency Caesarean deliveries after a trial of labour were associated with more neonatal admissions and operative complications. Conclusions: Trial of labour was associated with a shorter hospital stay. A successful trial of labour after one Caesarean was associated with the best outcome underscoring the importance of patient selection for a trial of labour.